2007
DOI: 10.1109/jqe.2006.886450
|View full text |Cite
|
Sign up to set email alerts
|

Raman Scattering and Nd$^{3+}$ Laser Operation in NaLa(WO$_{4}$)$_{2}$

Abstract: Abstract-The continuous-wave laser operation of Nd-doped tetragonal NaLa(WO 4 ) 2 crystal is studied at room temperature by optical pumping in the spectral region overlapping AlGaAs diode laser emission. This crystal has inhomogenously broadened optical bands. From the room-temperature spectroscopic parameters determined it is found that the optimum Nd concentration for the 4 3 2 4 laser channels must be in the 3-5 at.% range. For = 11 2 and 13 2 channels ( 1 06 and 1.3 m) the most favourable polarization con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…The average concentrations in the fibers are summarized in the table 4. The absorption spectrum (figure 9) showed absorption bands of the neodymium trivalent cation (Nd 3+ ) in the NLW host (in the single-crystalline fiber shape) in accordance with data already reported at literature for bulk crystals [4]. All of the observed transitions were identified.…”
Section: Fiber Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…The average concentrations in the fibers are summarized in the table 4. The absorption spectrum (figure 9) showed absorption bands of the neodymium trivalent cation (Nd 3+ ) in the NLW host (in the single-crystalline fiber shape) in accordance with data already reported at literature for bulk crystals [4]. All of the observed transitions were identified.…”
Section: Fiber Characterizationsupporting
confidence: 87%
“…Stimulated emission has been obtained with this ion incorporated in at least 100 different host materials, and a higher power level has been obtained from Nd lasers than from any other four-level material [2]. Recent spectroscopic studies of Nd 3+ :NaLa(WO 4 ) 2 crystals have shown high luminescent quantum efficiency, moderate emission cross-section and FWHM large emission in the 1.06 and 1.35µm regions, making this material a promising active host for tunable solid state laser [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Tungstates are well-known classical self-activated luminescence materials, which can effectively absorb ultraviolet (UV) and X-ray, then simultaneously migrate the absorbed energy to the doped rare-earth ions through energy transfer, and give their characteristic emissions. Therefore, they are recently considered as promising host materials for rare-earth luminescent centers because of the special properties of WO 4 2-& Guixia Liu liuguixia22@163.com group [11][12][13][14]. From the report of Huang et al [15], it was seen that tungstate host essentially showed a little weaker blue emission at room temperature compared to the absorption in excitation spectrum, owing to efficient energy transfer from WO 4 2-group to activators.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, efficient laser operation with Nd 3þ [6], Yb 3þ [7,8], Tm 3þ [9,10] and Ho 3þ ions [11] has been reported. These materials have an important advantage as compared with their monoclinic counterparts where Na þ is replaced by K þ , i.e.…”
Section: Introductionmentioning
confidence: 99%